Prevalence and determinants of condom use among the youth in Malawi: evidence from the 2015/16 Malawi Demographic and Health Survey - Scholastica Eunice Jimu; Lorretta F. C. Ntoimo; Friday E. Okonofua (BMC, 2023)
Abstract Background Unprotected sexual intercourse among the youth is common in Malawi. This has led to high rates of sexually transmitted infections (STIs), Human Immunodeficiency Virus (HIV), and unplanned pregnancies. The study investigated the prevalence and the determinants of male and female condom use for the prevention of sexually transmitted infections and unplanned pregnancies among the youth in Malawi. Methods The 2015/2016 Malawi Demographic and Health Survey (MDHS) data were used among 15 to 24-year-old male and female who had sexual intercourse four months preceding the survey. A total of 1543 male and 5143 female were selected from 3226 male and 10,367 female respectively and analyzed with SPSS version 20 using.descriptive, bivariate, and logistic regression. Results The study found a low prevalence (27.1%) of condom use among the youth in the last sexual intercourse within four months before the survey. More male (55.8%) used condoms than female (18.5%). The significant predictors of condom use among the male and female youth were: being sexually active (OR 0.39 CI 0.33-0.47), aged 20-24 (OR 0.80 CI 0.68-0.95), ever married (OR 0.07 CI 0.06-0.08), coming from central region (OR 0.56 CI 0.40-0.77), and southern region (OR 0.59 CI 0.42-0.83), residing in the rural area (OR 0.74 CI 0.61-0.90) and ever tested of HIV (OR 1.29 CI 1.03-1.55). Conclusion Having established low prevalence of condom use among the youth in Malawi, there is a need to scale up programs and policies that target the youth to practice safe sex, which will assist in addressing the challenges of STIs, including HIV, and preventing unplanned pregnancies in Malawi.